Analisis User Experience (UX) pada Aplikasi Segari Menggunakan HEART Metrics - Nurlailah; Ibnu Rusdi (Jurnal Teknologi, 2023)
The high number of their internet users is being marketed for business operators based on e-commerce. That is one Segari platform online expenditure that sells fresh materials quality. More than 3 thousand give users the critical. The writer to know what felt the user with UX when accessing the application Segari. Is expected to help to improve, developers create or maintain UX. HEART metrics are to identify the framework and measure the focus on user-centered Having 5 variables commonly used for measuring experience user quality (UXQ), consisting of Happiness, Engagement, Adoption, Retention, and Task success. While in terms of the measurement of research and analysis of data, research is both quantitative research. For data processing using the PSPP application for windows version 1.6.2, the percentage of the total score is 53 % that can be assumed that the application of Segari has managed to create an immersive experience good for their users through variable happiness, engagement, and adoption, retention, and task success. The level of happiness based on variable user experience, engagement, adoption ', retention, and task success calculated based on 32 questions 2 has an average point of the lowest question on variable Task success . This means the experience user application Segari is quite satisfactory and succeeded in creating a good experience but not yet overall since there are some questions each variable has an average point of lowest and requires improvement.